2024
DOI: 10.1038/s41467-024-49325-7
|View full text |Cite
|
Sign up to set email alerts
|

Emergent normal fluid in the superconducting ground state of overdoped cuprates

Shusen Ye,
Miao Xu,
Hongtao Yan
et al.

Abstract: The microscopic mechanism for the disappearance of superconductivity in overdoped cuprates is still under heated debate. Here we use scanning tunneling spectroscopy to investigate the evolution of quasiparticle interference phenomenon in Bi2Sr2CuO6+δ over a wide range of hole densities. We find that when the system enters the overdoped regime, a peculiar quasiparticle interference wavevector with arc-like pattern starts to emerge even at zero bias, and its intensity grows with increasing doping level. Its ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…The normal electrons, if they exist, may be present in the form of phase separation either in the real space or reciprocal space as shown in the STM measurement of the overdoped Bi2201 077405-4 samples. [6,7] In principle, ARPES can distinguish normal electrons from superconducting electrons because they behave differently in the superconducting state. The normal electrons will have a band that crosses the Fermi level and produce spectral weight at the Fermi level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The normal electrons, if they exist, may be present in the form of phase separation either in the real space or reciprocal space as shown in the STM measurement of the overdoped Bi2201 077405-4 samples. [6,7] In principle, ARPES can distinguish normal electrons from superconducting electrons because they behave differently in the superconducting state. The normal electrons will have a band that crosses the Fermi level and produce spectral weight at the Fermi level.…”
Section: Resultsmentioning
confidence: 99%
“…The normal fluid is clearly observed by STM in the superconducting state. [6,7] But in heavily overdoped Bi2212, the normal fluid is negligible in the superconducting state. In overdoped LSCO, it is found that the superfluid density decreases with increasing doping.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation